2018
DOI: 10.1111/cgf.13431
|View full text |Cite
|
Sign up to set email alerts
|

Maps and Globes in Virtual Reality

Abstract: a) Exocentric globe (b) Flat map (c) Egocentric globe (d) Curved map Figure 1: Four interactive visualisations for geographic data in Virtual Reality (VR). AbstractThis paper explores different ways to render world-wide geographic maps in virtual reality (VR). We compare: (a) a 3D exocentric globe, where the user's viewpoint is outside the globe; (b) a flat map (rendered to a plane in VR); (c) an egocentric 3D globe, with the viewpoint inside the globe; and (d) a curved map, created by projecting the map onto … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 35 publications
(38 reference statements)
2
61
1
Order By: Relevance
“…also Huang et al 2018). However, VR is currently defined and operationalized in ambiguous ways, e.g., as virtual globes (Yang et al 2018), VRGIS (Boulos et al 2017) or Virtual Geographic Environments (VGE;…”
Section: Geovisualization Immersive Environmentsmentioning
confidence: 99%
“…also Huang et al 2018). However, VR is currently defined and operationalized in ambiguous ways, e.g., as virtual globes (Yang et al 2018), VRGIS (Boulos et al 2017) or Virtual Geographic Environments (VGE;…”
Section: Geovisualization Immersive Environmentsmentioning
confidence: 99%
“…Marriot et al [9] argue that egocentric data views, such as proposed by Kwon et al [8], [27], may increase user engagement. However, a study by Yang et al [28] showed that maps explored from an egocentric perspective led to lower performance than any other representation in VR (an exocentric view, a flat map view, and a curved map view). We share the belief that egocentric data views are a unique strength of virtual environments to provide a new perspective on the data that cannot be easily obtained on a desktop screen.…”
Section: Related Workmentioning
confidence: 99%
“…However, there has been little research into the effectiveness of such visualisation using modern head-tracked binocular HMDs. The most relevant study by Yang et al [65] compared task performance for three standard map reading tasks-distance comparison, area comparison and direction estimation-using different 2D and 3D representations for the Earth. They compared a 3D exocentric globe placed in front of the viewer, an egocentric 3D globe placed around the viewer, a flat map (rendered to a plane in VR) and a curved map, created by projecting the map onto a section of a sphere curved around the user.…”
Section: Immersive Analyticsmentioning
confidence: 99%
“…The disadvantage of a globe representation is that the curved surface of the globe causes foreshortening and only half of the globe can be seen at one time. An alternative is to use a 3D egocentric representation for the globe in which the user is placed inside a large sphere [65][66][67]. This suffers from similar drawbacks to the exocentric globe: foreshortening and inability to see more than half of the Earth's surface.…”
Section: Representation Of Reference Spacementioning
confidence: 99%
See 1 more Smart Citation